A modular, multi-arm concentric tube robot system with application to transnasal surgery for orbital tumors. (February 2021) - Bruns, Trevor L.; Remirez, Andria A.; Emerson, Maxwell A.; Lathrop, Ray A.; Mahoney, Arthur W.; Gilbert, Hunter B.; Liu, Cindy L.; Russell, Paul T.; Labadie, Robert F.; Weaver, Kyle D.; Webster, Robert J.
In the development of telemanipulated surgical robots, a class of continuum robots known as concentric tube robots has drawn particular interest for clinical applications in which space is a major limitation. One such application is transnasal surgery, which is used to access surgical sites in the sinuses and at the skull base. Current techniques for performing these procedures require surgeons to maneuver multiple rigid tools through the narrow confines of the nasal passages, leaving them with limited dexterity at the surgical site. In this article, we present a complete robotic system for transnasal surgery featuring concentric tube manipulators. It illustrates a bagging concept for sterility, and intraoperatively interchangeable instruments that work in conjunction with it, which were developed with operating room workflow compatibility in mind. The system also includes a new modular, portable surgeon console, a variable view-angle endoscope to facilitate surgical field visualization, and custom motor control electronics. Furthermore, we demonstrate elastic instability avoidance for the first time on a physical prototype in a geometrically accurate surgical scenario, which facilitates use of higher curvature tubes than could otherwise be used safely in this application. From a surgical application perspective, this article presents the first robotic approach to removing tumors growing behind the eyes in the orbital apex region, which has not been attempted previously with a surgical robot.